2016
DOI: 10.1111/his.13014
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of invasion and lymphovascular invasion in squamous cell carcinoma of the floor of the mouth: an interobserver variability study

Abstract: Interobserver agreement in the diagnosis of LVI was substantial. The POI at the 50% and 20% cut-offs is moderately reproducible, and has prognostic value in FOM SCC. Further studies are necessary to establish the optimum quantitative cut-off for the POI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
15
1
Order By: Relevance
“…Regarding the single histopathological features, Sawair et al found moderate Kappa values for keratinisation (0.48) and even worse ones for pattern of invasion 33. Analysis of Kappa values for the pattern of invasion as defined by the Royal College of Pathologists34 resulted in kappa values between 0.43 and 0.58 in a study by Beggan et al ,35 whereas Heerema et al found values between 0.25 and 0.5853 and Chang et al a value of 0.72 36. Interobserver agreement of the HR model was good with κ =0.84 37.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the single histopathological features, Sawair et al found moderate Kappa values for keratinisation (0.48) and even worse ones for pattern of invasion 33. Analysis of Kappa values for the pattern of invasion as defined by the Royal College of Pathologists34 resulted in kappa values between 0.43 and 0.58 in a study by Beggan et al ,35 whereas Heerema et al found values between 0.25 and 0.5853 and Chang et al a value of 0.72 36. Interobserver agreement of the HR model was good with κ =0.84 37.…”
Section: Discussionmentioning
confidence: 98%
“…Agreement was not improved with the use of CD31 (κ = 0.26) or D2‐40 (κ = 0.32). LVSI assessment in squamous carcinoma of the floor of the mouth was performed on H&E slides from 58 cases by three pathologists using their own criteria. This resulted in substantial agreement for LVSI (κ = 0.64), comparable to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Reproducibility of LVSI assessment has also been studied in the context of other tumours, such as hepatocellular carcinoma (HCC), colorectal cancer and squamous cell carcinoma of the floor of the mouth . In the HCC study, inter‐ and intraobserver reproducibility of six pathologists were analysed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast histopathologically superficial cortical erosion is insufficient to classify a patient as having pathological bone involvement (pT4a) as this has not consistently been shown to be of prognostic significance. Instead invasion into the medullary cavity is necessary pathologically to be called positive bone invasion 12, 13. This is a likely contributory factor to the reported low specificity of both CT and MRI in the evaluation of mandibular bone invasion by SCC 6, 16, 17, 18.…”
Section: Discussionmentioning
confidence: 99%